Current Management of Advanced and Metastatic Renal Cell Carcinoma - Ather, M Hamad; Masood, Nehal; Siddiqui, Tahmeena (Urology Journal, 2010)
Introduction: Unresectable renal cell carcinoma (RCC) is a technically incurable condition. Historically, RCC is resistant to chemotherapy and radiotherapy. Cytokine therapy was until recently considered the mainstay of treatment. However, responses are modest. Improvement in the understanding of the biology of RCC, particularly the hereditary types, is providing the basis for novel therapeutic targets. Our aim was to review the clinical utility of various systemic agents and surgery in the management of advanced RCC and suggest practice guidelines in the light of current literature.Materials and Methods: Evidence was collected by review of current literature, guidelines of the American and European associations and the national comprehensive cancer network.Results: Treatment of advanced RCC has recently undergone a major change with the development of targeted agents and potent angiogenesis inhibitors. Small-molecule multikinase inhibitors that target vascular endothelial growth factor receptors have a favorable toxicity profile and can prolong time to progression and preserve quality of life when used in newly diagnosed or previously treated patients; bevacizumab enhances the response rate and prolongs disease control when added to interferon-alpha. Temsirolimus, a mammalian target of rapamycin inhibitor, prolongs the survival duration of patients with poor-risk disease. All currently available agents have variable toxicity profile and they, at best, improve survival by a few months. Surgery still has a significant role in the management of stage IV RCC. Conclusion: Supportive care and surgery remain the mainstay of treatment even in the management of advanced and metastatic RCC. Systemic therapeutic agents are showing promising results.